2016
DOI: 10.1364/ol.41.000634
|View full text |Cite
|
Sign up to set email alerts
|

Tapered fluorotellurite microstructured fibers for broadband supercontinuum generation

Abstract: Fluorotellurite microstructured fibers (MFs) based on TeO2-BaF2-Y2O3 glasses are fabricated by using a rod-in-tube method. Tapered fluorotellurite MFs with varied transition region lengths are prepared by employing an elongation machine. By using a tapered fluorotellurite MF with a transition region length of ∼3.3  cm as the nonlinear medium and a 1560 nm femtosecond fiber laser as the pump source, broadband supercontinuum generation covering from 470 to 2770 nm is obtained. The effects of the transition regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 30 publications
1
18
1
Order By: Relevance
“…BaF 2 was included for the purpose of reducing the OHd content, and the introduction of Y 2 O 3 was for better thermal stability in fiber drawing process as well as providing a higher glass transition temperature raised by the high melting temperature of Y 2 O 3 . In 2016, Wang et al achieved SC generation extending from 0.47 μm to 2.77 μm (zero-dispersion wavelength at 1730 nm) using a tapered TeO 2 -BaF 2 -Y 2 O 3 (TBY)-based microstructured fiber whose core was surrounded by six air holes [81].…”
Section: (A) the Cross Section Of The Die Used For Extrusion (B) Elementioning
confidence: 99%
“…BaF 2 was included for the purpose of reducing the OHd content, and the introduction of Y 2 O 3 was for better thermal stability in fiber drawing process as well as providing a higher glass transition temperature raised by the high melting temperature of Y 2 O 3 . In 2016, Wang et al achieved SC generation extending from 0.47 μm to 2.77 μm (zero-dispersion wavelength at 1730 nm) using a tapered TeO 2 -BaF 2 -Y 2 O 3 (TBY)-based microstructured fiber whose core was surrounded by six air holes [81].…”
Section: (A) the Cross Section Of The Die Used For Extrusion (B) Elementioning
confidence: 99%
“…Furthermore, other structural parameters of tapered fibers, such as taper waist diameter and transition region length can affect the SC results. Some researchers have demonstrated that wider SC generation can be achieved in a tapered fiber with a smaller diameter [150][151][152]. A small fiber diameter produces a small A eff in ChG tapered fibers, which increases the laser power intensity at the taper waist.…”
Section: Sc Generation In Chg Tapered Fibersmentioning
confidence: 99%
“…Also, the flexibility and mechanical strength of MNFs have been able to offer great advantage to demonstrate various microstructures as sensing head, such as loop, coil, and optical coupler [29][30][31]. In addition, thanks to the strong field confinement and tunable dispersion, MNFs have been applied to nonlinear optics [32][33][34][35][36]. Furthermore, MNFs have been used as quantum light sources based on spontaneous four-wave mixing (SFWM) process, that are suitable for directly connecting to other fiber-based system with negligible coupling loss [37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%